Bio-hydrogen production from palm oil mill effluent (POME): A preliminary study. (27th July 2016) - Norfadilah, Nik; Raheem, Abdul; Harun, Razif; Ahmadun, Fakhru'l–Razi
Abstract: Raw palm oil mill effluent (POME) from a cooling pond and sludge from anaerobic pond of the POME treatment plant at Labu palm oil mill were collected for the study. The treatment of POME was carried out under anaerobic fermentation process, with an objective to produce bio-hydrogen via microflora. The experiments were conducted in 500 mL bioreactor under mesophilic operation at 37 °C with different pH (4.5, 5.0, 5.5, and 6.0) and sludge percentage values (2.5, 5, 7.5, and 10% (w/v)). The source of inoculum was used in POME sludge as hydrogen producing bacteria. From batch experiments, the maximum hydrogen production yield obtained was 5.988 ± 0.5 L H2 /L-med at 10% POME sludge (w/v) with an optimum pH of 5.5 and mesophilic temperature of 37 °C. Methane free biogas consist of 36% maximum hydrogen and 64% carbon dioxide was produced during the process. Highlights: Bioreactor of 500 mL was successful used to produce hydrogen from POME via microflora. High pH, sludge percentage and higher temperature favored hydrogen production. The highest production of hydrogen was achieved at pH 5.5, 10% (w/v) POME sludge and 37 °C temperature. Methane free biogas consisted of 36% hydrogen and 64% carbon dioxide was produced during the process.